The role of IL-18 in intestinal immune regulation - Harrison, OJ (2013)
Elevated levels of the cytokine interleukin-18 (IL-18) are found in many chronic inflammatory disorders, including inflammatory bowel disease (IBD). However, the role of IL-18 in mucosal immunity and inflammation is not well understood. At mucosal and environmental interfaces, Th17 cells have been shown to contribute to protection from pathogenic infection. In contrast, regulatory T (Treg) cells maintain intestinal homeostasis by preventing aberrant inflammatory responses to the resident microbiota. We demonstrate that under homeostatic conditions, colonic Th17 cells highly express IL-18 receptor (IL-18R1) and that intestinal epithelial cell production of IL-18 acts directly on CD4+ T cells to limit colonic Th17 differentiation. Furthermore, whilst IL-18R1-signalling is dispensable for induction of colitis, we observed a critical role for IL-18R1-signalling in Foxp3+ Treg mediated control of colitis. Together, these studies demonstrate that the intestinal epithelium regulates colonic CD4+ T cell responses through production of the cytokine IL-18.